Labor market returns to college education with vocational qualifications - Sylvi Rzepka (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
In a context of demographic change, European governments seek ways to keep the skill set of the labor force flexible. One option to achieve this goal is widening access to college education to non-traditional students, such as those vocationally trained. Assessing whether this is a promising approach, I investigate what kind of labor market returns German non-traditional students can expect after enrolling in college rather than continuing with a vocational training-based career. Relying on the Adult Cohort of the National Educational Panel Study I use propensity score-adjusted regressions to estimate the average treatment eff ect on those that enroll in college based on vocational qualifications. The findings suggest high opportunity costs because treated individuals have an up to 67 percent lower employment probability while being enrolled. After this initial phase individuals exhibit a similar employment level and job stability as those that continue with a vocational training-based career. All treated individuals take up more prestigious jobs. Enrolling in college is on average associated with at most 43 percent higher life-time earnings compared to earnings when continuing with a vocational training-based career. However, recouping the opportunity costs of enrolling in college is a lengthy and risky process. – – Aufgrund des aktuellen demographischen Wandels, der mit einem Fachkräftemangel einhergeht, sucht die Politik nach Strategien, das Qualifikationsniveau der Erwerbsbevölkerung den neuen Herausforderungen anzupassen. Die Öffnung des tertiären Bildungsbereichs für Personen ohne Abitur stellt eine mögliche Maßnahme dar. Dieser Artikel untersucht, ob es sich für Individuen in Deutschland auszahlt, mit einer beruflichen Qualifikation ein Studium aufzunehmen im Vergleich zu Personen, die ihre ausbildungsbasierte Laufbahn fortsetzen. Ich schätze hierfür die Auswirkungen einer Immatrikulation an einer Hochschule auf die berufliche Laufbahn mit Hilfe der Erwachsenenstichprobe des Nationale Bildungspanel sowie Propensity Score und Regressionsmethoden. Die Ergebnisse deuten kurzfristig auf hohe Opportunitätskosten der beruflich qualifizierten Studierenden hin, da sie zu Beginn eine bis zu 67 Prozent niedrigere Wahrscheinlichkeit haben, erwerbstätig zu sein, als jene, die eine ausbildungsbasierte Karriere verfolgen. Langfristig erreichen sie jedoch dasselbe Niveau an Erwerbstätigkeit und Arbeitsplatzstabilität wie jene, die eine ausbildungsbasierte Laufbahn einschlagen. Zudem arbeiten beruflich Qualifizierte nach dem Studium in prestigeträchtigeren Berufen und erzielen maximal 43 Prozent höhere Lebenseinkommen. Die anfänglichen Opportunitätskosten auszugleichen dauert allerdings sehr lange und ist risikobehaftet.
Keywords: I21; J24; J62; 330; Educational choice; vocational training; tertiary education; occupational mobility